Treated Like a Child : Age Discrimination and Children's Rights - Daly, Aoife,; Leviner, Pernilla,; Stern, Rebecca Thorburn, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
One of the core principles of the UN Convention on the Rights of the Child is non-discrimination. However, little attention has been given to how this principle can protect children from discrimination because of age and childhood. This anthology brings together experts from children's rights studies to explore both overall issues related to discrimination of children, as well as non-legitimate differential treatment in specific contexts - including climate crisis, child labour, migration, healthcare, and child protection. Attention is drawn to the potential to advance children's rights in the framework of nondiscrimination in relation to children as a group.